From a better use of instrumentation to new detection methods in NMR and EPR spectroscopy - Verstraete, J-B (2022)
NMR and EPR spectroscopy are two of the most important techniques to get quantitative, structural or dynamical information on molecular systems. After covering the fundamentals of these magnetic resonance techniques, this thesis explores ways to improve the usage of current spectrometers and to create new instruments altogether using different detection methods with quantum sensing.